Investigation of ionospheric losses for the 'O+ + O2 ? O2 + + O' reaction during the solar eclipse - Yasar, Mehmet (Iop Publishing Ltd, 2021)
In this study, the response of the loss terms for the 'O+ + O-2 -> O-2 (+) + O' reactive reaction, which is an important charge transfer process in the upper ionosphere, to the partial solar eclipse on March 29, 2006 over Kharkov city located in the European mid-latitude was analyzed together with the reference days of 28 and 30 March. The measurement data were obtained from the Kharkov incoherent scatter radar. The loss terms for O+ + O-2 reaction increased at the time of maximum covering and changed inversely proportional to the ionospheric height. The maximum loss terms were obtained at heights of 252, 303 and 353 km on the eclipse day, while it was seen at the 399 km on March 30. For the four altitudes, the maximum and minimum (except 353 and 399 km) values on the eclipse day were seen at different time intervals. The important finding of this analysis is that the solar eclipse effect on the loss terms gives different results at the upper and lower heights and the complexity of the ionospheric behaviour with the increase in altitude. Another important result of this analysis reveals that the effect of solar eclipse on ionospheric loss terms is greater on the day after the eclipse compared to the day before the eclipse. The results of this study show that eclipse-induced mechanisms such as electric field, neutral wind changes, lunar tides, atmospheric gravity waves (AGWs) and diffusion can continue to impact the ionosphere during and after the solar eclipse.
Keywords: solar eclipse; ionosphere; chemical reactions